Music Training (Zikr) Is Superior To Autogenic And Progressive Muscle Relaxation Training To Increase Endurance Level Among University Sultan Zaina,l Abidin's Athletes - Rohayah, Husain; Ahmad Zubaidi, A.latif; Hazliza, Razali; Khairi, Che Mat; Marhasiyah, Rahim; Nordin, Simbak (2014)
Introduction: This study was designed to compare the effects of three different relaxation techniques, namely progressive muscle relaxation (PMRT), autogenic relaxation (AGRT) and Music Training (MT) following endurance exercise among University Sultan Zainal Abidin's Athletes. Methodology: Fifty university athletes aged l8 to 25 (mean age: 19.8 * 1.7) received either AGRT (n:12), PMRT (n:14), MT(n:14) or C no training C (n:10) biweekly for four weeks. The mood state were measured using the Brunel Mood Scale (BRUMS) , endurance level, heart rate, oxygen consumption and lactate accumulation parameters were measure at pre and post intervention. Results & Discussion: The mean differences of endurance level among athletes differed significantly pre and post intervention (F:4.963, p:0.005.). For the psychological parameters repeated measures ANOVA with a Greenhouse-Geisser correction revealed that total mood distress (TMD) differed statistically significantly between time points (F :132.24, P < 0.0001). For the physiological parameters oxygen consumption and lactate accumulation differed significantly between groups of relaxation techniques (F: 2.3ll,P < 0.05). Post hoc tests using the Bonferroni correction revealed that MT is the most effective, followed by PMT and AGRT respectively. Conclusion: We conclude that all the three type of relaxation training is effective to increase endurance level among athletes. All those relaxation training produced significantly changes in physiological parameters namelyYO2 max and serum lactate; as well as a reduction in positive mood scores. We also found that music training using the sentimental and arabic lyric ("zikr") which is similar to meditation is the superior method of relaxation training, followed by progressive muscle relaxation and autogenic relaxation.